Apresentação da Temática Especial 3: Educação Antirracista e Futebol - Mezzaroba, Cristiano; Vasques, Daniel Giordani; Silva , Silvio Ricardo da; Soares , Antonio Jorge Gonçalves (Cadernos do Aplicação, 2024)
Apresentação da Temática Especial 3: Educação Antirracista e Futebol